LINC01608 activated by YY1 facilitate hepatocellular carcinoma progression by modulating the EGFR/ERK axis. (25th November 2022) - Han, Mengzhen; Liu, Furong; Li, Xinxin; Zhang, Hongwei; Pan, Yonglong; Liu, Yachong; Zhu, He; Liang, Huifang; Chen, Xiaoping; Liao, Zhibin; Zhang, Zhanguo; Zhang, Bixiang
Abstract: Background: Long non‐coding RNAs (LncRNAs) have been demonstrated to associate with a variety of cancers. However, the mechanisms of LncRNAs in hepatocellular carcinoma (HCC) progression are still not fully clarified. Methods: LINC01608 expression level in HCC and adjacent normal tissues was detected by real‐time‐quantitively PCR (RT‐qPCR) in clinical samples and in situ hybridization (ISH) in tissue microarray. Several functional assays were performed to determine the biological effects of LINC01608 in HCC cells in vitro, while subcutaneous xenograft models and lung metastasis models in nude mice and immunohistochemistry (IHC) results showed the role of LINC01608 in HCC progression in vivo. The combination of LINC01608 with miR‐875‐5p and target genes was elucidated by dual‐luciferase report assays, RNA immunoprecipitation (RIP) assays and fluorescence in situ hybridization (FISH) assays. Finally, bioinformatics analysis and chromatin immunoprecipitation (CHIP) were performed to investigate the mechanism of Yin Yang‐1 (YY1) regulating LINC01608 transcription. Results: LINC01608 was overexpressed in HCC tissues, and high LINC01608 expression predicted poor overall survival (OS) and disease‐free survival (DFS) in HCC patients. LINC01608 could promote HCC cell proliferation, migration, invasion and epithelial‐mesenchymal transition (EMT) in vitro and in vivo. Furthermore, we demonstrated that LINC01608 could sponge to miR‐875‐5p and activate the EGFR/ERK pathway. Moreover, we identified transcriptional factor YY1 could bind to the promoter of LINC01608 and induce its transcription. Conclusion: LINC01608 could serve as a promising prognostic biomarker of HCC. YY1‐activated LINC01608 could promote HCC progression by associating with miR‐875‐5p to induce the EGFR/ERK signalling pathway. This discovery might provide therapeutic strategies for HCC.